2019
DOI: 10.1039/c9ra05490a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional lubricant additive based on difluoroboron derivatives of a diphenylamine antioxidant

Abstract: Difluoroboron derivatives of an antioxidant with excellent antioxidation and antiwear properties provide a new strategy for metal-free and phosphorus-free multifunctional additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…By mixing two selected antioxidants (AOLA and EAOLA) into tung oil, respectively, the OOT of tung oil was increased from 121.9°C to 138.5°C and 146.5°C, respectively, indicating that all selected antioxidants oxidants can improve the OOT of tung oil to a certain extent. Among the two antioxidants, the antioxidant EAOLA, with more phenolic hydroxyl groups, has the best antioxidant performance [35], which further proves that EAOLA is the most suitable antioxidant for tung oil.…”
Section: Effect Of Lubricant Additives On Oxidation Stabilitymentioning
confidence: 71%
“…By mixing two selected antioxidants (AOLA and EAOLA) into tung oil, respectively, the OOT of tung oil was increased from 121.9°C to 138.5°C and 146.5°C, respectively, indicating that all selected antioxidants oxidants can improve the OOT of tung oil to a certain extent. Among the two antioxidants, the antioxidant EAOLA, with more phenolic hydroxyl groups, has the best antioxidant performance [35], which further proves that EAOLA is the most suitable antioxidant for tung oil.…”
Section: Effect Of Lubricant Additives On Oxidation Stabilitymentioning
confidence: 71%
“…This phenomenon is attributed to the small steric hindrance of the imine group, allowing radicals to easily capture hydrogen. In addition, Wang et al [127,128] even introduced B and F elements into SPD and SSPD molecules to prepare BSPD, SSPD-BF1, and SSPD-BF2 compounds, as shown in Figure 16. TGA indicated that the weight loss phenomenon of BSPD occurs at relatively high temperatures, and the corresponding temperatures for BSPD at 5% and 95% weight loss are 328 and 414 • C, respectively.…”
Section: Phenolic Amine Complex and Its Derivativesmentioning
confidence: 99%
“…Some efforts have been made towards the synthesis of heterocyclic compounds such as triazoles based multifunctional additives free from SAPS (sulfated ash, phosphorus, and sulfur) 12 . Many attempts have been made in the direction of modification in boron and molybdenum‐based compounds (molybdenum‐containing mercaptotriazine and difluoroboron derivatives of a diphenylamine) provide reaction sites and introduce multifunctionality due to the availability of polar groups 13,14 . Borated PIBSI is a widely used commercial multifunctional additive to demonstrate dispersancy, anti‐oxidant and anti‐wear activities.…”
Section: Introductionmentioning
confidence: 99%
“…12 Many attempts have been made in the direction of modification in boron and molybdenum-based compounds (molybdenum-containing mercaptotriazine and difluoroboron derivatives of a diphenylamine) provide reaction sites and introduce multifunctionality due to the availability of polar groups. 13,14 Borated PIBSI is a widely used commercial multifunctional additive to demonstrate dispersancy, anti-oxidant and anti-wear activities. Dodecenylsuccinic amide of Nphenyl-p-phenylenediamine also reported in the literature as multifunctional additive as anti-oxidant, anti-corrosive, lubricity improver, deposit control additive for engine oil application.…”
Section: Introductionmentioning
confidence: 99%